Comparative Evaluation of Remineralization Agents on Early Enamel Caries Lesions: An In Vitro Study - Dr. P.R. Sanjaya,; Dr. Tripuravaram Vinay Kumar Reddy,; Dr. Sravani Bejugam, (The Bioscan, 2025)
Dental caries remains one of the most prevalent chronic conditions worldwide, with early enamel demineralization being the first detectable clinical manifestation. The progression of these incipient lesions is reversible, provided that effective remineralization strategies are employed at the earliest stage of development. Recent advances in preventive dentistry have led to the development of various remineralization agents, each with unique mechanisms of action and potential benefits. This in vitro study was designed to comparatively evaluate the efficacy of three commonly used remineralization agents: fluoride-based formulations, casein phosphopeptide–amorphous calcium phosphate (CPP-ACP), and bioactive glass in reversing early enamel caries lesions. A total of extracted sound human premolars were sectioned and subjected to controlled demineralization to simulate initial carious lesions. The samples were then randomly divided into experimental groups based on the remineralization agent applied, along with a control group maintained in artificial saliva. Over a defined treatment period, each group was exposed to its respective agent under standardized laboratory conditions. The degree of remineralization was assessed using surface microhardness testing, scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDX) to evaluate changes in surface integrity, mineral deposition, and calcium-phosphate ratio. The findings demonstrated that all tested agents produced measurable improvements in enamel hardness and mineral recovery compared to the control group. Fluoride treatments significantly enhanced surface microhardness, confirming their long-established role in caries prevention. CPP-ACP displayed superior penetration into subsurface lesions, promoting uniform mineral deposition and stabilizing amorphous calcium phosphate within the lesion body. Bioactive glass exhibited pronounced surface remineralization, characterized by the formation of a hydroxycarbonate apatite layer that effectively sealed enamel porosities. Among the groups, CPP-ACP and bioactive glass exhibited higher potential for lesion repair beyond the superficial layer, suggesting their advantages in deeper lesion management. This comparative evaluation highlights that while fluoride remains a cornerstone in caries prevention, novel agents such as CPP-ACP and bioactive glass offer promising adjunctive or alternative solutions in managing early enamel caries lesions. Their complementary mechanisms of action, ranging from enhancing resistance to acid attack to restoring the mineral balance within enamel, underscore the importance of personalized preventive strategies. Clinically, these findings reinforce the value of integrating biomimetic and bioactive remineralization technologies into preventive protocols, potentially reducing the need for invasive restorative interventions.